2019
DOI: 10.1038/s41598-019-46154-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity participation and the risk of chronic diseases among South Asian adults: a systematic review and meta-analysis

Abstract: South Asia specific reviews on the role of physical activity (PA) domains on chronic disease prevention are lacking. This study aimed to systematically review published literature to identify the association between PA domains and chronic diseases and to provide summary estimates of the strength of association. Nine electronic databases were searched using the predefined inclusion criteria which included population (South Asian adults 40 years or older), exposure (PA or sedentary behaviour) and outcome (type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
0
20
1
1
Order By: Relevance
“…In addition, considering the results of previous studies reporting that those who benefit from health insurance are more likely to receive health checkups depending on the nature of the health insurance system in Korea, chronic diseases could be effectively managed through modifying the nature of the insurance provided. Previous studies have shown that health behavior factors related to chronic diseases include smoking, drinking, exercise, body mass index, and regular life and eating habits [7,29,36,48,49]. However, in this study, drinking and smoking did not have a statistically significant effect on the prevalence of chronic diseases, and these results are different from those of existing research.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, considering the results of previous studies reporting that those who benefit from health insurance are more likely to receive health checkups depending on the nature of the health insurance system in Korea, chronic diseases could be effectively managed through modifying the nature of the insurance provided. Previous studies have shown that health behavior factors related to chronic diseases include smoking, drinking, exercise, body mass index, and regular life and eating habits [7,29,36,48,49]. However, in this study, drinking and smoking did not have a statistically significant effect on the prevalence of chronic diseases, and these results are different from those of existing research.…”
Section: Discussioncontrasting
confidence: 99%
“…Rapid economic growth, high health-care costs, lifestyle changes, and population aging have been associated with an increased prevalence of chronic diseases worldwide. Chronic diseases may cause complications, and thus, require continuous care and are among the types of diseases with high health-care costs due to their long disease duration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In our sample, more than 60% of participants indicated that COVID-19 pandemic influenced severely in their physical activity levels. Because of low physical activity levels, individuals may experience an increased risk for the development or worsening of health conditions as weight gain, high blood pressure, glycemic and lipid control and impaired fitness [36,37]. Additionally, moderate intensity physical activity has been recommended as a non-pharmacological, inexpensive, and viable way to cope with COVID-19 virus, also due to the benefits on the immune system and its ability to reduce systemic inflammation [13,38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, physical inactivity, obesity, smoking, and diabetes mellitus increased the risk for CVD [1]. Currently, sedentarism has been recognized as a primary risk factor, and physical exercise is associated with a decreased mortality rate from coronary artery disease [2]. Thus, a sedentary lifestyle is characterized as any waking behavior whose energy expenditure is less than 1.5 METs (metabolic equivalent), sitting, reclining, or lying down.…”
Section: Introductionmentioning
confidence: 99%